APPLYING CORPUS LINGUISTICS TO ENGLISH TEXTBOOK EVALUATION: A CASE IN VIET NAM - Nguyet, Huynh Thi Thu; Long, Nguyen Van (VNU Journal of Foreign Studies; Vol 36 No 6DO - 10.25073/2525-2445/vnufs.4632, 2020)
Looking at textbook evaluation from a corpus linguistics perspective, this paper compares two sets of textbooks used at senior high school in Vietnam and evaluate the effectiveness of the new one, centering on lexical resources at word level, particularly individual words and phrasal verbs. As for the comparison of the wordlist in general, the two corpora, taken from the two sets of textbooks, were analysed by Antconc software to extract the wordlist, then the two wordlists are compared by Venny 2.1.0 to see the similarities and differences. The research reveals a quantifiable evaluation of the lexical resources, tapping into the mutual and exclusive words, as well as examining lexical complexity of the two sets of textbooks. Unlike conventional textbook reviews focusing on grammar, this study is one of the first attempts to evaluate textbooks efficiency from corpus linguistics perspective, which in turn contributes to the improvement of the current English textbooks in Viet Nam, as well as a source of consideration for curriculum design worldwide.